Emotionality as a prerequisite for success in pedagogical activities - Čebykinas, A. (Psichologija, 1988)
The paper on the basis of theoretical and experimental investigations shows that in case the emotional communicative characteristics of applicants are taken into account success in their future pedagogical work is predetermined. These characteristics can be of use as a criterion of professional selection at the pedagogical institutes.
Keywords: emotionality; success in pedagogical activities; emotions